Oblivious, paranoid, and disclosed negative ties: An examination of the mechanisms underlying the relationship between negative ties and job performance. (4th January 2018) - Al‐Atwi, Amer Ali
Summary: This study extends the literature on negative relationships by proposing a classification of negative ties that involve oblivious, paranoid, and disclosed ties. This classification provides a guide to explore the causal mechanisms that underlie the relationship of negative ties to individual job performance (productivity and task performance). Specifically, we hypothesize that (a) disclosed and oblivious ties can constrain opportunity to perform through structural empowerment and (b) disclosed and paranoid ties can constrain willingness to perform through psychological empowerment. Drawing on data from 121 faculty members working in a public college located in the south of Iraq, we found structural empowerment and psychological empowerment to be the mediating variables in the negative ties–performance relationship. The theoretical and practical implications of these findings are discussed.